Financial Policy Workshops : The Case of Kenya. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1985)
This book written by the staff of the IMF Institute, offers a series of workshops on Kenya that are used as a case study in the Institute's course on Financial Analysis and Policy for officials of IMF member countries. The workshops combine theory and practice for a better understanding of the use of major financial policy instruments in the management of national economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet